ENGLISH-REVISITING THE IMPLICATIONS OF PAKISTAN’S COLD WAR ALIGNMENT ON ITS ISLAMIC AND POLITICAL LANDSCAPE - Habib Ali Katohar; siraj Ahmed Soomro; Irshad Ali Wassan (دی اسکالر)
This research venture attempts to revisit the repercussions of Pakistan’s alignment with the U.S. bloc during the reign of the Cold War against the spread of the former communist Soviet Union in the Asian region on its political landscape and Islamic identity. The study also seeks to explore the research gaps associated with Pakistan’s role as a key player in the interplay of the Cold War that changed its political dynamics and shaped religious identity. The findings of the study suggest that Pakistan’s role as a key player in the U.S. war against the spread of communism in the Asian region brought significant geopolitical and strategic changes coupled with shaping unprecedented religious and cultural identities. For instance, the emergence of religious extremism and hatred, sectarianism, terrorism, and militancy resulted from the refugee influx from Afghanistan caused by the Cold War rivalry between the United States and the former Soviet Union on Afghan soil. Finally, the paper fosters an understating of contemporary political and religious challenges to Pakistan by navigating the historical alignment of the country with the United States.